Complications of Lower Body Lift Surgery in Postbariatric Patients. Issue 9 (September 2016) - Poodt, Ingrid G.M.; van Dijk, Martine M.; Klein, Steven; Hoogbergen, Maarten M.
Abstract : Background: There is an exponential rise of patients with massive weight loss because of bariatric surgery or lifestyle changes. The result is an increase of patients with folds of redundant skin that may cause physical and psychological problems. The lower body lift is a procedure to correct deformities in the abdomen, mons, flanks, lateral thighs, and buttocks. Complication rates are quite high and could negatively affect the positive outcomes. The purpose of this study is to assess complication rates and to identify predictors of complications to optimize outcomes for patients after lower body lift surgery. Methods: A retrospective analysis of 100 patients who underwent a lower body lift procedure was performed. The patients were reviewed for complications, demographic data, comorbidities, smoking, highest lifetime body mass index, body mass index before lower body lift surgery, percentage of excess weight loss, and amount of tissue excised. Results: The overall complication rate was 78%. Twenty-two percent of the patients had major complications and 56% had minor complications. There is a linear relationship between body mass index before lower body lift surgery and complications ( P = 0.03). The percentage of excess weight loss (odds ratio [OR] 0.97; 95% confidence interval [CI] 0.92–1.00), highest lifetime body mass index (OR 1.08; 95% CI 1.01–1.15), body mass index before lower body lift surgery (OR 1.17; 95% CI 1.02–1.33), and smoking (OR 7.74; CI 0.98–61.16) are significantly associated with the development of complications. Conclusions: This study emphasizes the importance of a good weight status before surgery and cessation of smoking to minimize the risk of complications.